SGLT2 knockout prevents hyperglycemia and is associated with reduced pancreatic β-cell death in genetically obese mice. Issue 5 (3rd September 2018) - Jurczak, Michael J.; Saini, Saumya; Ioja, Simona; Costa, Diana K.; Udeh, Nnamdi; Zhao, Xiaojian; Whaley, Jean M.; Kibbey, Richard G.
ABSTRACT: Inhibition of the sodium-glucose co-transporter type 2 (SGLT2) has received growing acceptance as a novel, safe and effective means to improve glycemic control in patients with type 2 diabetes. Inhibition of SGLT2 lowers the renal glucose threshold and reduces plasma glucose by promoting glucose excretion in urine. Both animal studies and clinical trials in man suggest that SGLT2 inhibition has the potential to improve pancreatic β-cell function by reducing glucose toxicity. However, there is limited data exploring how reducing glucotoxicity via SGLT2 inhibition affects rates of β-cell proliferation and death throughout life in the context of insulin resistance and type 2 diabetes. SGLT2 −/− mice were backcrossed to the db/db strain to produce littermate control db/db -SGLT2 +/+ and experimental db/db -SGLT2 −/− mice. Mice were euthanized at 5, 12 and 20 weeks of age to collect plasma for glucose, insulin, lipid and cytokine measures, and pancreata for histological analysis including determination of β-cell mass and rates of proliferation and death. SGLT2 deletion in db/db mice reduced plasma glucose as early as 5 weeks of age and continued throughout life without changes in plasma lipids or cytokines. Reduced plasma glucose levels occurred in parallel with an increase in the relative β-cell volume and reduced frequency of β-cell death, and no apparent change in rates of β-cell proliferation. These data add to a growing body of evidence demonstrating that improved glycemic control achieved through SGLT2 inhibition can preserve β-cell function and endogenous insulin secretion by reducing glucose toxicity and rates of β-cell death.